Prediction of Narcissistic Personality Tendencies in University Students in Terms of Some Variables - Derya Ekici (Journal of Research in Social Sciences and Language)
The purpose of this study is to investigate whether perceived parental attitudes and subjective well-being in university students predict narcissistic personality tendencies. The study was conducted with 1377 students studying at various faculties of İnönü University in the academic year of 2014-2015 and participated in the study voluntarily. Of the obtained data, 1146 of which were completely filled were included in the study. The personal information form prepared by the researcher was used as the data collection tool in the study to obtain information about the Narcissistic Personality Inventory, Positive and Negative Affect Scale, Life Satisfaction Scale, Parent Attitude Scale and demographic variables. The data were analyzed with SPSS 18.0 package program. Multiple linear regression analysis was used to analyze the data. Parents' attitudes, which are perceived to be very low predictive levels of subjective well-being and sub-dimensions of narcissistic personality tendencies, were found not to predict sub-dimensions of narcissistic personality tendencies.